Female Psychopathy and Mortality - Vaurio, Olli; Lähteenvuo, Markku; Kautiainen, Hannu; Repo-Tiihonen, Eila; Tiihonen, Jari (Frontiers in Psychiatry, 2022)
The mortality of female psychopaths has scarcely been investigated. To estimate the association between psychopathy and mortality, data from subjects having been in forensic psychiatric assessments at Niuvanniemi Hospital during 1984–1993 were linked to the data from the National Death Registry. Sixteen psychopathic females scoring 25 points or higher in the PCL-R scale (psychopaths) were followed up for a median (IQR) 21 (17–25) years and 41 offenders scoring less than 25 on the PCL-R (non-psychopathic offenders) for 22 (17–25) years. In both psychopath and non-psychopath offender groups, the mortality was significantly higher (p<0.01) than in the general population, being over 12-fold among psychopathic and over 6-fold among the non-psychopathic offenders.